Limonin, an AMPK Activator, Inhibits Hepatic Lipid Accumulation in High Fat Diet Fed Mice - Wang, Si-wei; Lan, Tian; Chen, Hang-fei; Sheng, Hao; Xu, Chun-yi; Xu, Li-feng; Zheng, Fang; Zhang, Feng (Frontiers in Pharmacology, 2022)
NAFLD is the most prevalent liver disease in human history. The treatment is still limited. Limonin is known to be a main bitter principle in citrus. Despite some studies demonstrated the effect of limonin on reducing inflammation and oxidative stress, few reported the function of limonin in the regulation of glucose and lipid metabolism. In the current study, for the first time, we uncovered that limonin inhibited hepatic lipid accumulation and fatty acid synthesis in HFD fed mice. Using AMPK inhibitor and AMPK deficient C. elegans, we revealed the effect was dependent on the activation of AMPK. We found that limonin activated AMPK through inhibition of cellular energy metabolism and increase of ADP:ATP ratio. Furthermore, the treatment of limonin induced AMPK mediated suppression of the transcriptional activity of SREBP1/2. Our study suggests that limonin may a promising therapeutic agent for the treatment of NAFLD.